O gênero publicitário na sala de aula: uma proposta Didático-pedagógica a partir da perspectiva da teoria Do ethos discursivo - Cordeiro, Hugo Bulhões (2015)
As a qualitative research this study aims to support the work of the teacher of Portuguese Language with the advertising genre from the design of the discursive ethos and to propose didactic sequences and activities in order to contribute to the pedagogical practices. It starts from the relation of advertising text with its behavioral manner, the ethos, expressed in identifying production context of the advertising texts. The corpus of this research consists of advertisements of Friboi brand in the Veja magazine in May and April of 2014. The ethos is composed from arguments that mark the way of expressing itself, instituting desires and acts of consumption, through its incorporation by the reader listed from the basic theory of Discourse Analysis - specifically the concepts of Dominique Mangueneau. Moreover, other authors in this study include different perspectives, such as: Zygmunt Bauman, Patrick Charaudeau, Stuart Hall, Eni P. Orlandi and Nelly de Carvalho. So it is from this magnifier feature analysis of prospects for the advertising text for Linguistics that this work begins to diversify into other areas, such as Sociology, Philosophy, as well as Speech Analysis, which justifies the evidence plan given by this work to the ethos theory. That's why, interdisciplinary, this dialogue disassociates the plan of textual analysis in Portuguese classes from a reductionist perspective of interpretive possibilities.